REPRESENTATION OF COCA COLA AS AMERICAN MULTICULTURAL ICON IN THE TV ADVERTISEMENT AMERICA IS BEAUTIFUL - Benita Amalina (Universitas Gadjah Mada, 2014)
On February 2, 2014, Coca Cola released a new television advertisement titled “America is Beautiful” during Super Bowl event. The advertisement shows American multicultural families having a good time together. What makes this advertisement different from the previous ones, is the usage of a patriotic song America is Beautiful as the musical background. This research examines how Coca Cola as a brand represents the multicultural America through this advertisement. The result shows that it is affected by the historical values and the fact that the CEO of Coca Cola blatantly advertise multicultural America by encouraging and supporting the immigrants.